Manfaat Ekonomi Sertifikasi Organik pada Usaha Tani Mete di Desa Dukuh, Kecamatan Kubu, Kabupaten Karangasem - BAGUS UTAMA EMTIEN; I WAYAN BUDIASA; PUTU UDAYANI WIJAYANTI (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2018)
The Economic Benefits of Organic Certification on Cashew Farming in the Dukuh Village, Kubu Sub-District of Karangasem Regency Demand for organic cashew nuts in the international market is very high. The existence of organic certificate gives positive impact for cashew farmers, especially in increasing the selling price. Subak Abian Buana Kusuma is one of subak abian in Karangasem regency which conducts certified organic farming from certification institution of International Institute for Marketecology (IMO) Switzerland. Organic cashew certification is done by international certification agency IMO (Institute for Marketecology) Switzerland with the support of PT. PMA (Profil Mitra Abadi) and Dinas Kehutanan dan Perkebunan Kabupaten Karangasem to Subak Abian Buana Kusuma which is technically certified by ICS (Internal Control System). Revenue per hectare of certified organic farmers is Rp. 28,111,004,74 and non-organic farmers is Rp. 12,560,166.20, with a percentage of 119% greater income per hectare of organic farmers while the income per kg of organic farmers is Rp. 21,238.16 and non-organic farmers is Rp. 11,721.14 / kg with a percentage of 81% larger per kilogram of organic farmers. Premium price received by farmers is Rp.9000,00 with the cost of certification per kg is Rp. 163.00. Organic premium received by farmers is Rp. 9,517,02 / kg. The RC ratio of Subak Abian Buana Kusuma and Pandan Sari were 4.69 and 2.87 respectively, and the Profit Rate was 369% and 187%, compared to 5% for 5% said to be very worthy to be cultivated. The value of t arithmetic> t table (2.34> 2.05), means that the income per hectare of organic cashew farms is greater than non-organic cashew nut production.